Pembaharuan Hukum Ketenagakerjaan dalam Sistem Pengupahan Berdasarkan Prestasi Pekerja: Sebuah Konkretisasi dari Radbruch Formula - Fitria Puspita Rachmandita (CV Rewang Rencang, 2021)
In this developing era, money is one of the most important things. Therefore, there are many disputes between workers and employers. So the existence of an Employment Act is one way for the government to reduce Employment Problems, for example, problems in wages. Minimum Wages and Overtime Wages as a basic wage and allowances are still a dispute in wages because the Indonesian people consider that the calculation of the Minimum Wage, both Regional and Provincial is not appropriate. So there is a need for new reformulations such as increasing wages according to the achievements made by each employee so that created justice in society.